Early trajectories of motor skills in infant siblings of children with autism spectrum disorder. Issue 3 (26th November 2021) - Patterson, James W.; Armstrong, Vickie; Duku, Eric; Richard, Annie; Franchini, Martina; Brian, Jessica; Zwaigenbaum, Lonnie; Bryson, Susan E.; Sacrey, Lori‐Ann R.; Roncadin, Caroline; Smith, Isabel M.
Abstract: Delays in motor development are not considered a core feature of autism spectrum disorder (ASD). Yet, recent studies of infant siblings of children with ASD suggest that early delays in motor skills may be associated with later delays in developmental areas considered to be core features of an ASD diagnosis. While these studies demonstrate the longitudinal association between core features and motor delays observed at single time points, there is considerable interest in studying the trajectories of motor development over the first 3 years of life. To accomplish this, we investigated early trajectories of motor development in a cohort of 499 infant siblings of children with ASD and 176 children with no family history of ASD. Data for the current study were drawn from the prospective, multi‐site, Canadian Infant Sibling Study. We evaluated trajectories of fine and gross motor development over the first 3 years using group‐based trajectory modeling. Our results show that membership for both fine and gross motor trajectory groups was related to expressive language skills, receptive language skills, ASD symptom severity scores, and diagnostic classification at age 3. These results provide evidence that the trajectory of a child's early motor development may have important prognostic implications in ASD. Lay Summary: Difficulties with motor skills are not included in current diagnostic criteria for autism spectrum disorder (ASD) but have gained attention in recent studies of ASD in early life. By tracking development of infants over the first 3 years of life, our work shows that motor impairments may set the stage for later impairments in ASD. In infants with an elevated likelihood of developing ASD, the patterns of early motor development may predict the probability of receiving an ASD diagnosis, later language skills, and severity of symptoms.